Preparation and Evaluation of Celecoxib Nanoemulsion for Ocular Drug Delivery - Salimi, Anayatollah (Asian Journal of Pharmaceutics (AJP), 2017)
Introduction: Poor bioavailability of drugs from ocular dosage forms is mainly due to the tear production, nonproductive absorption, transient residence time, and impermeability of corneal epithelium. The aim of the present study was to design, characterize of a novel nanoemulsion (NE) system as an ocular delivery system for celecoxib (CXB) and to evaluate its physicochemical characteristics and rabbit corneal permeability to enhance the penetration of the drug. Methods: CXB NEs were prepared by testing its solubility in oils, surfactants, and cosurfactants. Utilizing pseudoternary phase diagram, the optimum ratios were chosen and full factorial design was used with 3 variables at 2 levels for preparing eight formulations. The prepared NEs were evaluated regarding their viscosity, pH, particle size, differential scanning calorimetry thermograms, stability, in vitro drug release, and corneal rabbit permeability. Results and Discussion: The results showed that the mean droplet size range of NE formulations was in the range of 6.96-26.65 nm and pH was 6.5-6.9, respectively. Viscosity range was 118-245 cps. Drug release profile showed that 82.6% of the drug released in the 24 h of the experiment. The maximum and minimum drug permeated percentage through rabbit cornea was observed in NE component (NEC)-5 (15.73%) and NEC-1 (6.1%), respectively. All NE formulations with different compositions and properties significantly increased partitioning, flux, and permeability coefficient from rabbit cornea. Dapp and Papp parameters in NEC-3 and NEC-5 formulation were 0.0233 cm2 h−1, 0.13 cm/h, and 46.62, 7.23 times higher than those of control (CXB suspension, 1%), respectively. The flux (Jss) of CXB from NEC-5 was 0.65 mg cm−2 h−1, 21.68 times higher than those of control. Conclusion: This present study showed that any change in content and composition of NEs could be changed physicochemical properties and permeability parameters during drug permeation from NE formulations. The phenomenon may be due to alteration of the cornea structural changes in the presence of NECs.